An innovative C-shaped yielding metallic dampers for steel structures. (December 2021) - Farsi, A.; Amiri, H.R.; Dehghan Manshadi, S.H.
Highlights: C-shape damper dissipates the input energy of the earthquake with a replaceable sacrificial C-shape element. Stable hysteretic behavior and being easily replaceable after failure are prominent features of C-shaped fuse. C-shape passive damper can protect main elements of structure from plastic deformation and failure. C-shape damper works as appropriate energy absorber component. Abstract: This paper proposed a new passive metallic damper, termed C-Shaped Damper (CSD), for a braced frame structure. The proposed system dissipates the earthquake energy using some sacrificial C-Shaped elements and protects the main elements of structures from plastic deformation and failure. This study investigated energy dissipation and behavior of CSD through numerical and analytical methods. For this purpose, parametric investigations were carried out analytically and numerically. Parametric studies considered the effect of vertical and horizontal diameters of CSD, thickness, and depth of the CSD on its behavior. A good agreement was observed between analytical and numerical results. The numerical results demonstrate that the yielding force was directly related to the thickness and depth of the CSD. Also, by the increasing horizontal diameter, yielding force and energy dissipation decreased. The results indicated suitable energy dissipation and steady hysteretic behavior of the CSD under cyclic loading with a salient characteristic such as being easily replaceable after failure.